El Aspecto Lúdico del e-Learning: El juego en entornos virtuales de aprendizaje - Margulis, Lucio (2015)
The use of 'Information and Communication Technologies' (ICT's) is revolutionizing the way of learning, teaching and playing of new generations and modern organizations.We can appreciate how in many cases people learn more due to their surroundings (classmates, learning situations, elements and institutions with which they interact), than because of the specific course teacher. In this article I propose we share a particular perspective concerning the playful aspect of the multimedia contents for education projects based on 'e-learning' (electronic learning) and 'Blended Learning' (mixed format that combines the best of the real and virtual world)